Systematic Review: Self-harm in Adolescent Bullying Victims - Hasniati, Nur Eti; Adawiyah, Rabiatul; Shabron, Rifatul Hasanah Ahmad (Yayasan Adra Karima Hubbi, 2024)
Nowadays, bullying behavior is very common, especially among teenagers and young adults. Bullying is intentionally aggressive behavior, which aims to make other people feel uncomfortable, cornered or intimidated. Bullying has a very negative effect on the growth and development of teenagers. For example, increased depression and stress, low self-esteem, sleep disorders, and the emergence of self-harm behavior and suicide. Self-harm is a detrimental action in the form of self-harm. And if it continues, it will lead to more serious problems such as suicide. The aim of this systematic review is to describe the causes of self-harm in adolescents who experience bullying. The method used in this paper is to use a systematic literature method originating from the Google Scholar and Scopus databases. With a publication range from 2019 to 2023. These journals use English and Indonesian in full-text form. After a series of data sorting processes, 18 papers were obtained that met the inclusion criteria. With the results of three main factors that influence self-harm actions in adolescent victims of bullying. Among them are psychological, social and physical factors.